Virgilio dalla 'Vita nova' al 'Convivio' (Quaderni di Gargnano, 2022)
This paper explores the presence of Virgil in Dante's Vita nova and Convivio. While the Latin poet plays a fundamental role in the Commedia, he occupies a markedly less exceptional position in these earlier works, despite respectful references to his mastery of poetic style. A shift occurs in the Convivio's fourth book, which accords special importance to the figure of Aeneas and to the catabasis that will become a decisive source of inspiration for the Commedia. In Convivio IV, moreover, Virgilian references are fundamental to Dante's presentation of his new intuition that Providence authorized the foundation of the Roman empire by a divinely-elected people. Only after this decisive "Virgilian turn" does it become possible for Dante to imagine an imperial poem, with Virgil acting as guide for its protagonist along a journey through the afterworld.Il contributo esamina la presenza di Virgilio nella Vita nova e nel Convivio. Se nella Commedia una tale presenza sarà fondamentale, nelle prime opere di Dante, Virgilio, pur citato con rispetto come maestro di stilistica poetica, non assume invece un rilievo eccezionale. La svolta si ha nel IV trattato del Convivio, dove acquistano uno spazio speciale la figura di Enea e la sua catabasi, episodio che sarà decisivo nell'ideazione della Commedia. In questo trattato i riferimenti virgiliani svolgono poi una funzione basilare nella presentazione delle nuove idee di Dante sulla provvidenzialità della fondazione dell’impero e sulla divina elezione del popolo romano a tale missione. Solo dopo una tale "svolta virgiliana" diventa possibile per Dante immaginare un poema imperiale in cui Virgilio guida il protagonista in un viaggio nell'aldilà.
Keywords: Dante; Dante e Virgilio; Vita nova; Convivio; Dante and Virgil